2020
DOI: 10.1108/ijpsm-12-2018-0277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implementation of International Public Sector Accounting Standards on Nigeria’s financial reporting quality

Abstract: Purpose The purpose of this paper is to examine the effects of the implementation of the International Public Sector Accounting Standards (IPSAS) on Nigeria’s financial reporting quality. Design/methodology/approach The study employed a survey research design to determine the effects of the implementation of the IPSAS on Nigeria’s financial reporting quality. Partial Least Square 3(SmartPLS 3) technique of analysis was applied to achieve the research objective. Findings The study found that accountability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 15 publications
6
24
0
Order By: Relevance
“…A similar study was carried out by Muraina (2020) who examined the effects of the implementation of the International Public Sector Accounting Standards (IPSAS) on Nigeria's financial reporting quality. The study employed a survey research design to determine the effects of the implementation of the IPSAS on Nigeria's financial reporting quality.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A similar study was carried out by Muraina (2020) who examined the effects of the implementation of the International Public Sector Accounting Standards (IPSAS) on Nigeria's financial reporting quality. The study employed a survey research design to determine the effects of the implementation of the IPSAS on Nigeria's financial reporting quality.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Several studies have been carried out in different parts of the world on the benefits of IFRS and on the perception of accounting practitioners on the transition and convergence to the IFRS (Mohamed et al 2019;Dabbicco and Mattei 2020;Albu et al 2020;Ntoung et al 2020;Muraina 2020;Sharairi 2020;Joshi et al 2008;Ionascu et al 2014).…”
Section: Empirical Literaturementioning
confidence: 99%
“…On the other hand, presence of international pressure and economic crisis influenced the adoption of accrual based IPSAS. Muraina (2020) reported the existence of significant and positive relationship between quality of financial reporting under IPSAS and accountability. This signifies that accountability levels in public sectors have been improved as the outcome of adoption of IPSAS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regardless of the best intended objectives of adoption of IPSAS, as evidenced above, developing countries have not harvested its desired outcome Mbelwa et al 2019). Previous studies have concentrated on the effects of adoption of IPSAS, harmonisation in the public sector financial reporting, legitimation of accrual accounting and transparency as well as accountability (Matekele and Komba 2019;Mbelwa et al 2019;Miraj and Wang 2019;Mnif Sellami and Gafsi 2019;Muraina 2020;Kartiko et al 2018;Baskerville and Grossi 2019). Other scholars have dedicated their studies on economic and institutional factors affecting implementation of accrual based IPSAS (Mnif Sellami and Gafsi 2019;Brusca et al 2013;Iyoha and Owolabi 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, based on the results of research Alijarde (2002) found that Local Government Financial Reports were found to be used in decision making for finance directors, government management, and other potential users such as auditors, financial entities, and other stakeholders, with one of them being used to assess the extent to which financial accountability and compliance with budget execution. As research from Muraina and Dandago (2019) has conducted research in which the research objective is to examine and analyze the effect of IPSAS implementation on the quality of the Nigerian government's financial statements. The findings of this research are accountability which is an indicator of the IPSAS variable that has a positive and significant effect on the quality of Nigeria's financial statements.…”
Section: Introductionmentioning
confidence: 99%